Acculturation of Javanese Islam and Mapalus Culture in The Development of Islamic Economic Tradition in Tondano - Hadi, Rahmini; Shafrani, Yoiz Shofwa; Nurhayati, Laily (Ijtimā iyya Journal of Muslim Society Research, 2024)
Diversity allows the emergence of merging existing cultures into a new culture that does not take away the essence of the previous culture. The success of Tondano Javanese Village in maintaining the existence of economic traditions, especially in the agricultural sector, also plays a role in balancing the economy in the Tondano region. Mapalus is synonymous with the life cycle of the Minahasa community which is closely related to religious values. Development of Javanese Islam in Tondano began to occur after the group of Kiai Mojo and his followers consisting of approximately 60 men, established an association place for them to settle and live there, namely "Kampung Java". In addition, the development is also getting stronger after they are in a relationship assimilation through marriage with indigenous Minahasa women who at that time the majority adhered to Christianity. The Muslim community living in Minahasa influenced the development of the existing mapalus uyang culture. Mapalus is a form of local wisdom of the indigenous people of Tondano adapted by the Muslim community from Java. Then from Joanne et al (in Senduk, 2016) Added one other form of mapalus, namely arisan. This Arisan is one of the prominent forms of social interaction between members of the North Minahasa community. Its function is to help each other in the economic field based on family values. In general, this social gathering is one of the associations in terms of distributing funds. This concept is in great demand by the lower middle class because it is considered easy to fulfill one's direct desires, so it is considered to be able to pay in installments (Muhaisin & Syarbaini, n.d.). In practice, the forms of the collection also vary, such as money, groceries, jewelry, building materials, etc. Unlike the arisan practice implemented in Tondano Java Village, the form is an association to be able to divide work into agricultural and plantation activities. So in each activity, the agricultural and plantation production process will be divided based on its working group